Peningkatan Nilai CBR Laboratorium Rendaman Tanah dengan Campuran Kapur, Abu Sekam Padi dan Serat Karung Plastik - Widianti, Anita (Universitas Muhammadiyah Yogyakarta, 2009)
Bearing capacity of a subgrade is one of the parameters to design the thickness of road pavement. Beside the bearing capacity, swelling behavior of subgrade must be in a narrow range to avoid crack of the pavement. This paper presents an effort to improve the soaked design California Bearing Ratio (CBR) and swelling value of soil by stabilizing with lime-rice husk ash and strengthened by randomly placed plastic fiber. In this study, the portions of lime and rice husk ash were set constant to the value of 12% and 24%, respectively. Amount of waste plastic sack fibers was used in this experiment ranging from 0.1% to 1.2% of dry weight of mixtures. The samples were tested at 7 and 14 days after mixing. The results show that the soaked design CBR value increases to 867%. As a result, swelling value decreases from 62% to 100%. The optimal improvement of the soaked design CBR was found at 0.2% of plastic sack fibers.